2011
DOI: 10.1063/1.3635777
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of Ag nanoislands on Ag(100) by adsorbed sulfur

Abstract: Sulfur accelerates coarsening of Ag nanoislands on Ag(100) at 300 K, and this effect is enhanced with increasing sulfur coverage over a range spanning a few hundredths of a monolayer, to nearly 0.25 monolayers. We propose that acceleration of coarsening in this system is tied to the formation of AgS 2 clusters primarily at step edges. These clusters can transport Ag more efficiently than can Ag adatoms (due to a lower diffusion barrier and comparable formation energy). The mobility of isolated sulfur on Ag(100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…[1][2][3] This relates to the broader emerging theme that metal surfaces can be dynamic or fluxional in nature (rather than static or frozen) under operating conditions during catalysis. 4,5 With regard to additiveenhanced transport on coinage metals, previous studies revealed a contrasting dramatic enhancement for Ag(111) 6 versus limited enhancement for Ag(100) 7 upon exposure to S. A similar dramatic enhancement was also observed for Cu(111). 2 While no experiments are currently available for Cu(100), we expect limited enhancement as for Ag(100).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…[1][2][3] This relates to the broader emerging theme that metal surfaces can be dynamic or fluxional in nature (rather than static or frozen) under operating conditions during catalysis. 4,5 With regard to additiveenhanced transport on coinage metals, previous studies revealed a contrasting dramatic enhancement for Ag(111) 6 versus limited enhancement for Ag(100) 7 upon exposure to S. A similar dramatic enhancement was also observed for Cu(111). 2 While no experiments are currently available for Cu(100), we expect limited enhancement as for Ag(100).…”
Section: Introductionmentioning
confidence: 78%
“…For higher coverages, island decay was so fast (occurring in less than the acquisition time for a single STM image) that it could not be quantified by STM imaging. In experiments for Ag on Ag(100) at 300 K, 7 the decay of 10 nm 2 islands roughly 5 nm away from an extended step was monitored as a function of y S . The decay time decreases from 70 min at y S E 0.035 ML to 30 min at y S E 0.13 ML, corresponding to only a modest increase in decay rate by a factor of 2.3.…”
Section: Methodsmentioning
confidence: 99%
“…Thiolates adsorbed on Au(111) [8,28], and thiolates at the periphery of Au nanoclusters, form species that include linear S-M-S units [28,29]. Linear S-M-S complexes (without alkyl ligands) have also been postulated-but not observed directly-on the basis of DFT and experimental data for S/Ag(100) [14], and on the basis of DFT alone for S/Ag(111) [2]. These results suggest that the linear S-M-S unit has generic stability across coinage metals.…”
Section: Factors That Stabilize Cu-s Complexesmentioning
confidence: 99%
“…Recently, for instance, Parkinson et al have shown that CO interacts with Pd atoms adsorbed on a Fe 3 O 4 surface, forming a highly-mobile Pd-CO complex [3]. Other adsorbates that form mobile surface complexes with metals include hydrogen [4,5], oxygen [6,7], alkylsulfides [8], and-the subject of this study-sulfur [9][10][11][12][13][14]. The soft metals Cu, Ag, and Au, which are of great interest because of their catalytic and plasmonic properties, are expected to be particularly susceptible to this effect.…”
mentioning
confidence: 99%
“…These complexes are generally mobile and can even facilitate metal surface dynamics and mass transport across the surface. [8][9][10][11][12][13] More specifically, these complexes can destabilize metal nanostructures and can accelerate coarsening or sintering of arrays of nanoclusters via a reactive version of Ostwald ripening. 11,14 The modern tools of surface science-particularly scanning tunneling microscopy (STM), diffraction techniques, and density functional theory (DFT)-have proven powerful enough to decipher even intricate extended structures, but direct experimental observations of isolated complexes between adsorbates and metal atoms extracted from the surface have been limited, due in part to difficulties in imaging mobile species.…”
mentioning
confidence: 99%